Acute Coronary Syndrome in the Young - Risk Factors and Angiographic Pattern (Cardiovascular Journal, 2010)
Background: Coronary artery disease (CAD) is a worldwide health epidemic. Acute coronary syndrome is a potentially life-threatening condition and patient may die or become disabled in the prime of life. There is documented evidence that South Asian people develop CAD at a higher rate and also at an early age. If the affected individual is 40 yrs old or below, the tragic consequences are catastrophic. Methods: It was a retrospective observational study to find out the pattern of acute coronary syndrome in the young (40 years old or less) in a military hospital (CMH Dhaka) from July 2007 to July 2008 and to analyze the risk factors and the angiographic characteristics of coronary vessels. Consecutive 64 young patients including both male and female admitted into this hospital were the study subjects. Out of these patients 53 were males and 11 were females. Among these patients coronary risk factors and angiographic pattern were studied. 64 older patients with Acute coronary syndrome (age more than 40 years) were also studied. Results: Out of 64 young patients 15.6% patients presented to this hospital as UA, 9.37% presented as Non-Q MI, 28.12% Acute Anterior MI, 14.06% Acute Anteroseptal MI, 26.56% Acute Inferior MI, 6.25% Acute Infero-posterior MI. Smoking was the most common risk factor among these young patients. 64.06% patients were smoker. Dyslipidaemia was present among 50% patients, 37.55% were hypertensive, 15.62% were diabetic, and 15.62% were obese. SVCAD was the most common lesion and it was 53.12%. 26.56% patients had DVCAD and TVCAD was present among 20.31% patients. In the older group (more than 40 years) most common risk factor was dyslipidaemia (71.88%) and smoking was present among 48.43% patients. Conclusion: Young patients have a different risk factor profile in comparison with older patients. Smoking is a strong and quite common coronary risk factor in the young ACS patients who are 40 years or less. Risk factor identification and control is very crucial in the primary and secondary prevention in young patients with CAD. Keywords: Acute coronary syndrome; Risk factors; Coronary Angiography DOI: 10.3329/cardio.v2i2.6635Cardiovasc. j. 2010; 2(2) : 175-178